Relações entre resiliência, trauma e envelhecimento - Asnis, Tatiane Gil (2021)
Brazil is experiencing a rapid growth of the population over 60 years old, following a global trend. According to 2019 UN projections, within the group of older people, those aged 80 years or older, called long-distance, constitute the population segment that experiences the greatest growth worldwide. As you get older, each individual has their own way of dealing with changes, with life's own situations, and with the losses of aging. Losses that vary from individual to individual in order of appearance and intensity, but all of them inherent in the passage of time (loss of joviality, health, aesthetic beauty, musculoskeletal capacities, cognition, autonomy and ultimately independence). In addition to natural losses, most individuals are also exposed to at least one threat situation during the course of their lives, and the way they deal with these potentially disturbing events also differs. Individuals are differentiated by the fact that some manage to overcome crises and others do not, and in addition to aspects such as temperament, genetics, social and economic aspects, affective relationships with family and friends, the capacity for each individual's own resilience will be fundamental for this overcoming. Resilience is commonly defined as the individual's or family's ability to face adversity, be transformed by them, and overcome them. With the increase in life expectancy, and with the difficulties that come from aging, resilience has often been related to the later life phase, when it is proposed that its development can be a protective factor for psychic suffering resulting from the experiences of aging. In order to verify how much traumatic experiences throughout life are responsible for the development of resilience in the long-lived elderly individual, as well as to understand that other factors are associated with resilience, and thereby increasing knowledge about this population that has been growing every year, a semi-structured interview was conducted with five long-term elderly. Through the qualitative research methodology, both with regard to data collection and in relation to their analysis, this research led us to the following conclusions: 1) For resilience, there must be previous trauma. 2) Traumatic experiences cannot overflow with the capacity of each individual to deal with them. If there is this excess, trauma will be detrimental to the development of resilience, making the individual vulnerable to suffering and the development of psychopathological conditions. 3) Experiences of safe attachment in childhood are fundamental to develop resilience. 4) The ability to perform mourning work is directly related to resilience. 5) Mature defense mechanisms are related to resilient capacity, as well as immature ones show the difficulty of the individual in making flexibility and accepting the changes of aging. 6) Self-concepts are directly related to resilient capacity. 7) Spirituality helps in the resilient capacity of the individual, but it is not fundamental.